2022
DOI: 10.1002/jsfa.12300
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the relationship between conditions of ultrasonic‐assisted extraction of chia mucilage and viscosity

Abstract: BACKGROUND The application of chia mucilage still remains restricted due to the difficulty in achieving high extraction yields. The effect of ultrasonic‐assisted extraction (UAE) conditions (temperature, seed:water ratio and time) on the rheological properties of chia mucilage extracts and the relation to the proportion of translucent phase (TP) and opaque phase (OP) of the mucilage in the extract were evaluated. RESULTS UAE allowed the efficient extraction of chia mucilage from chia seeds. The desired overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…Even some reports are available with the use of response surface methodology (RSM) to understand the impact of these factors on techno-functional properties. 20,27,56,57 Interesting facts revealed from a review that hydration conditions have more impact on the yield of mucilage while the proximate composition is affected by the extraction and recovery method. 42 However, a review by Chiang et al 42 has explained the impact of the literature available up to 2021.…”
Section: Chia Seed Mucilage and Its Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even some reports are available with the use of response surface methodology (RSM) to understand the impact of these factors on techno-functional properties. 20,27,56,57 Interesting facts revealed from a review that hydration conditions have more impact on the yield of mucilage while the proximate composition is affected by the extraction and recovery method. 42 However, a review by Chiang et al 42 has explained the impact of the literature available up to 2021.…”
Section: Chia Seed Mucilage and Its Compositionmentioning
confidence: 99%
“…21,27,28,40,43,51,61 It is interesting to study the mechanism of reduction of mucilage yield at higher hydration time with increased temperature in the future. 56 According to the reports of Saporittis et al , 57 along with an increase in extraction time from 30–210 minutes, using a magnetic stirrer followed by 3 minutes of UAE has significantly affected the yield of mucilage. However, it was revealed that at lower extraction time, the yield was independent of the temperature, but along with an increase from temperature 25–65 °C, yield became more temperature dependent while extracting mucilage with ultrasound (3 minutes of treatment time).…”
Section: Chia Seed Mucilage and Its Compositionmentioning
confidence: 99%
See 3 more Smart Citations